ECONOMIC, ECOLOGICAL AND ENERGY EFFICIENCY OF HEMP CULTIVATION USING ORGANIC FARMING TECHNOLOGIES - Pylypchenko, А. V.; Piskovyi, М. B. (Scientific Progress & Innovations, 2021)
The main aim of each manufacturer of any product, including agricultural, namely hemp, is obtaining stable crop yield, handling and processing products that would ensure sufficient profitability, allow to con-duct expanded reproduction of the industry and to compete with other crops, also ensure environmental products friendliness and restore biological activity and soil fertility without losing any of the economic in-dicators. Considering the experience of countries with developed market economies and also own experience in recent years regarding the transition from classical or intensive system of agriculture to organic technol-ogies of agricultural production, we can state that, there are prospects for the actual development of the in-dustry in the future stipulated by the fact that Ukraine has certain potential opportunities and reserves to stabilize the state and speed up the development of hemp growing. In comparison with the classical technol-ogy of hemp growing, the organic system, on the one hand, relieves stressful situations (the influence of min-eral fertilizers and plant protection products) and, on the other hand, increasing the number of cultivations improves soil air balance, which promotes the reproduction and development of soil biota. The research conducted at the enterprises of “Arnika” group of companies in Hlobyne town, Poltava region, started in 2015. The obtained experimental data allowed to make changes in the elements of the technology of hemp organic cultivation and thus to stabilize biological soil activity, its structure, and its regenerative ability. At the same time, there were essential changes in the cost part, in particular, cutting down expenses on acquisi-tion of plant protection means and mineral fertilizers, their application and equipment to conduct these op-erations and also costs for purchasing harrows and cultivators for organic technologies which positively influenced hemp productivity during the transition from classical cultivation technologies to organic farming system. The research has shown that there are peculiarities, which we still have to reveal in the process of further work.